Proximate composition of para-grass (Brachiaria mutica) produced in integrated fish-fodder culture system (Bangladesh Journal of Animal Science, 2015)
An experiment was conducted to evaluate the effects of Pangasius pond sediment on the nutrient uptake by para-grass (Brachiaria mutica) during the period from March to October, 2011 in a Pangasius farm, Dhanikhola, Trishal, Mymensingh. Initially soil chemistry of Pangasius pond sediment and para-grass producing virgin soil was analyzed at the laboratory. The fodder was cultivated at various level of inorganic fertilizer with Pangasius pond sediment having three replications in each treatment. The size of each replication was 25 m2 (5m×5m). The fodder was harvested at the pre-flowering stage (45 days after transplantation). After first cutting, experimental plot was irrigated, and again after 45 days of first cutting second cutting was done. After proper collection and preparation the para-grass samples and rice straw, their proximate composition analysis was done. The nutrient content of para-grass was also compared with rice-straw being used as dairy feed. The analytical results indicated that the nutrients content of Pangasius pond sediment was higher than the virgin soil which was the stimulating factor for para-grass growth and production. The basic nutrients such as crude lipid and protein content of para-grass were found increasing from first to second sampling. However, crude lipid and protein of para-grass at second sampling was found much higher than those of rice straw. Application of Pangasius pond sediment as alternative source of fertilizer enriched nutrient content of para-grass much higher than those of rice straw. Therefore, it could be argued that higher level of lipid and protein content of para-grass is the stimulating factor to dairy cattle production under integrated aquaculturefodder grass production using Pangasius pond sediment.Bang. J. Anim. Sci. 2015. 44(2): 113-119